Bridging Faith and Technology: Digital Innovation in Islamic Economic Practices - Nudin, Nurdin; M. Amin, Sagir; Sofyan, Syakir (Institut Agama Islam Negeri Kendari, 2024)
The digital transformation of Islamic economics and business has accelerated with widespread internet adoption, creating new opportunities and challenges for Shariah-compliant commerce. This study examines the emergence and impact of digitalization in Islamic economic activities through qualitative research conducted in Palu City, Indonesia. Data was collected through in-depth interviews with 24 young Muslim entrepreneurs and observations of Shariah-compliant businesses across different scales. The findings reveal four key areas of digital transformation: Shariah-compliant e-commerce, Islamic financial technology (fintech), digital payment systems, and electronic zakat, infaq, sadaqah, and waqf (e-ZISWAF) platforms. These digital innovations have expanded market access, improved operational efficiency, and increased transparency in Islamic business practices while maintaining Shariah compliance. However, challenges remain in the areas of regulatory frameworks, technological infrastructure, and consumer trust. This research contributes to understanding how Islamic economic institutions are adapting to digital transformation while preserving religious principles.